Scattering matrix for the wave equation with finite radial potential in the two-dimensional space - Mil'man, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Expressions for partial scattering matrices $S_l(λ)$ are obtained for all naturall by using Adamyan's result, which establishes a universal relationship between the scattering matrix for the wave equation with finite potential in a even-dimensional space and the characteristic operator function of a special contraction operator, which describes the dissipation of energy from the region of the space containing a scatterer. It is shown that this problem can be reduced to the case of $l = 0$ for all even $l$ and to the case of $l = 1$ for all odd $l$.